EVALUASI PELAKSANAAN PEMBAYARAN PAJAK REKLAME DI UPTD DINAS PENDAPATAN DAERAH KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Fiki Andri Arko; Indra Safri (UIR Press, 2018)
Importance of local taxes as a cash receipts and local finances. to achieve this goal, local governments continue to improve and explore every potential. One source of revenue sizeable contribution and potential as a source of revenue is the advertisement tax. This study aims to identify and analyze the implementation of Advertisement Tax Payments in UPTD Department of Revenue District of Bengkalis Bengkalis. In this study, using the theory of Policy Evaluation according Winarno, indicators evaluating policies used include identifying the purpose of the program will be evaluated, the analysis of the problem, standardization activity, a measure of the level changes, the observed change of activities and indicators to determine the existence of impact , To know Evaluation of the advertisement tax payments in the District of Bengkalis the researchers took population and sample a total of 11 people including employees UPTD Revenue, and 26 people who are not paying taxes, while being key informants in this study is the Head of Revenue and Treasurer Recipients UPTD UPTD. The sampling technique is a technique Dispenda UPTD employee census and for people who do not pay taxes is purposive sampling. This study uses qualitative and quantitative data collection from respondents was conducted by distributing questionnaires, and selanjunya researchers conducted interviews, documentation and observation to know the results of the implementation of the payment of the advertisement tax. After data collection is done, then analyzed by using percentages to determine how many respondents stating done, quite materialize, or less accomplished. based on the analysis of the obtained results of the research done and it can be concluded that the implementation activities Payment of advertisement tax in UPTD Department of Revenue District of Bengkalis Bengkalis, from the employees that are in the category of